Mechanical properties of carrot fiber - epoxy composite (Baghdad Science Journal, 2012)
Interest has largely centered on the use of plant fibers to reinforce plastics, because these fibers are abundant and cheap. Carrot fibers (Curran) have been extracted from carrot, left over from carrot juice manufacture. The fibers of two sizes fine (50